The Potential of halophytes in managing soil salinity and mitigating climate change for environmental sustainability - Kathirvel Suganya; Ramesh Poornima; Paul Sebastian Selvaraj; E Parameswari -; P Kalaiselvi (Environment Conservation Journal, 2021)
Soil salinization is one of the foremost factors affecting global agricultural productivity. More than half billion hectares of agricultural land are unutilized due to excess saline condition. Hence, there is a great urge in exploring scientific interventions in restoring the saline affected areas and promote high productive and effective land utilization in order to respond to today's global concerns of food security. While a sound drainage system is required as a permanent solution to the soil salinity problem in order to regulate the water table, this option cannot be used in larger area with high energy and cost-intensity.Phytoremediation, a plant – based approach is one of the promising technology in enhanced dissolution of Ca levels along with sodium removal through cultivating suitable halophytes.During the process, the proliferation of roots, aggregate stability, hydraulic conductivity and nutrient availability increases. These improvement in soil quality enables the growth of less tolerant crops, enhances the overall ecosystem and climatic conditions by increasing carbon sequestration. In this perspective, the chapter focuses on halophytes, its kinds, the effects of salinity on soil physical, chemical, biological health, the influence of halophytes in stress management and on the function of halophytes in carbon sequestration.